Investment Decision-Making Among Students Using Prospect Theory in Behavioral Economics - Basri Bado; Hajar Dewantara (Fundamental and Applied Management Journal, 2024)
Investment decision-making is crucial in finance, particularly for students planning their financial futures. This study focuses on students at Universitas Negeri Makassar (UNM) to understand how psychological factors influence their investment decisions. Utilizing Prospect Theory from behavioral economics, the research examines key factors such as risk perception, profit expectations, and time preferences. The study involved a survey of UNM students, and the descriptive analysis reveals that students tend to make decisions influenced by behavioral biases, loss aversion, and risk preferences. The findings indicate that students are consistent in their financial decision-making but are significantly impacted by psychological biases, particularly in their tendency to avoid losses and their cautious approach to risk and uncertainty. Overall, the investment behavior of UNM students is shaped by the psychological factors outlined in Prospect Theory, highlighting their reliance on subjective perceptions and loss avoidance. This research provides valuable insights for developing more effective financial literacy strategies and promoting wiser investment decisions among students. Additionally, it contributes to the application of Prospect Theory in the context of student investment decision-making.